Thromboelastography Variables, Immune Markers, and Endothelial Factors Associated With Shock and NPMODS in Children With Severe Sepsis - Saini, Arun; Spinella, Philip C.; Ignell, Steven P.; Lin, John C. (Frontiers in Pediatrics, 2019)
Objective: Evaluate hemostatic dysfunction in pediatric severe sepsis by thromboelastography (TEG) and determine if TEG parameters are associated with new or progressive multiple organ dysfunction syndrome (NPMODS) or shock, defined as a lactate ≥2mmol/L. We explored the relationship between TEG variables, selective cytokines, and endothelial factors. Design: Prospective observational. Setting: Single-center, quaternary care pediatric intensive care unit. Patients: Children aged 6- months to 14- years with severe sepsis with expected PICU stay for >72 h. Interventions: None. Measurements and Main Results: Twenty-eight children were enrolled with median (IQR) age of 7.3 years (4.4–11.4), PELOD score (study day-1) of 11(1.25–13), and PICU length of stay of 10 days (5–28). TEG-defined hypercoagulable state occurred most commonly in 73% (94/129) of samples, followed by hypocoagulable state in 7.8% (10/129) and mixed coagulation state in 1.5% (2/129) of samples in the study cohort. In contrast, hypocoagulable state occurred most commonly in 66% (98/148) of samples based on standard coagulation parameters. In the seven children who developed shock with NPMODS compared to eight patients with shock without NPMODS and 12 patients with severe sepsis only, we found more profound coagulopathy [thrombocytopenia (p = 0.04), elevated INR (p = 0.038), low fibrinogen level (p = 0.049), and low TEG-G value (p = 0.01)] and higher peak of interleukin-6 (p = 0.0014) and IL-10 (p = 0.007). Peak lactate in the first 5 study days had moderate correlation with standard coagulation assays, TEG parameters, and selective cytokines. Peak lactate did not correlate with markers of endothelial activation. Lowest TEG -G value had moderate correlation with peak IL-10 (ρ −0.442, p =0.019), peak VCAM (ρ − 0.495, p = 0.007), and peak lactate (ρ −0.542, p = 0.004) in the first 5 study days. A combination of TEG-G value and IL-6 concentration best discriminated children with shock and NPMODS [AUC 0.979 (95%CI 0.929–1.00), p < 0.001]. Conclusion: This exploratory analysis of hemostasis dysfunction on TEG in pediatric severe sepsis suggests that while hypercoagulability is more common, a hypocoagulable state is associated with shock and NPMODS. In addition, TEG abnormalities are also associated with immune and endothelial factors. A larger cohort study is needed to validate these findings.